1971
DOI: 10.1139/p71-379
|View full text |Cite
|
Sign up to set email alerts
|

Emission Spectrum of the PO Molecule. Part II.2Σ–2Σ Transitions

Abstract: Rotational structure of emission bands of the PO molecule in the region 5300-3800 A is analyzed.The spectrum is attributed to 5 electronic transitions A2Z+-B2Z+, F2Z+-B2Z+, G 2 Z + -B 2 Z + , H 2 Z + -B 2 Z + , and I 2 Z + -B 2 Z + , where F, G , H , and I are the new electronic states and A and B are the upper states of the well-known y and B bands respectively. Practically all the new ' Z states are found to be perturbed. A qualitative account of these perturbations together with a deperturbation of certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 7 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…The existence of a 4rti state in PO similar to the 4ITi state of NO had been proposed by Couet et al, 31 Verma et al,12 and by Roche and Levebvre-Brion30 as the state responsible for the predissociations observed in the D2nr and B'2!! ; states.…”
Section: Non-rydberg Statesmentioning
confidence: 73%
See 1 more Smart Citation
“…The existence of a 4rti state in PO similar to the 4ITi state of NO had been proposed by Couet et al, 31 Verma et al,12 and by Roche and Levebvre-Brion30 as the state responsible for the predissociations observed in the D2nr and B'2!! ; states.…”
Section: Non-rydberg Statesmentioning
confidence: 73%
“…On the basis of the molecular constants for this state (in PO) estimated in analogy with the corresponding values of NO, it is concluded that these perturbations are due to the v = 16 level of the 4n; state. An approximate potential energy curve for this state has been given by Verma et al 12 and the molecular constants are summarized in Table IV.…”
Section: Non-rydberg Statesmentioning
confidence: 99%
“…The PO and PO + have been investigated extensively in experiment3–38. Further related references are given in many of the references cited here.…”
Section: Introductionmentioning
confidence: 99%
“…Henceforth, the PO radical became the subject of considerable work, and the spectroscopic properties were widely studied by emission and absorption spectroscopy, laser photoelectron spectroscopy, infrared (IR) spectra, and so on. In the 1960s and 1970s, much progress was achieved by Verma et al12–21 and Coquart et al22–28. Their studies led to the discovery of 22 electronic states and a considerable number of transition bands were observed amongst these states.…”
Section: Introductionmentioning
confidence: 99%